Exploring shared decision making in breast cancer care: A case-based conversation analytic approach. (9th June 2020) - Mahmoodi, Neda; Jones, Georgina; Muskett, Tom; Sargeant, Sally
Abstract : Shared decision making (SDM) is acknowledged as the gold standard of healthcare communication, particularly relevant to preference-sensitive care such as breast cancer treatment. However, research on patients' experiences shows a misalignment between clinicians' goals and the rhetoric regarding patients' empowerment during SDM for this treatment. This warrants detailed examination on the conversational dynamics of SDM, and this study aims to identify interactional features and social practices through which SDM is achieved. Fifteen audio recordings from adjuvant treatment breast cancer consultations were examined using the methodology of conversation analysis (CA), and recurrent patterns relevant for understanding SDM were identified. Boundary markers, rhetorical questioning and epistemic markers discouraged a shared orientation to patient participation, reinforcing perceived imbalanced doctor–patient power relations. Cues for SDM such as multi-turn utterances and spaces for transition were presented but not recognised by patients, resulting in sub-optimal two-way discussions about decision making. The findings also reveal that interactional practices were deployed that theoretically should have enabled patients to contribute to SDM. However, in reality these did not result in extended sequences of reciprocated contributions from practitioner and service user. SDM did not happen with the ease implied by current models, and the resultant interactions bore more similarity to expert-led, rather than collaborative, decision making